2017
DOI: 10.1111/famp.12326
|View full text |Cite
|
Sign up to set email alerts
|

A Model‐Based Cluster Analysis of Maternal Emotion Regulation and Relations to Parenting Behavior

Abstract: In a diverse community sample of mothers (N = 108) and their preschool-aged children (M = 3.50 years), this study conducted person-oriented analyses of maternal emotion regulation (ER) based on a multimethod assessment incorporating physiological, observational, and self-report indicators. A model-based cluster analysis was applied to five indicators of maternal ER: maternal self-report, observed negative affect in a parent-child interaction, baseline respiratory sinus arrhythmia (RSA), and RSA suppression acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Descriptive statistics and correlations for variables of interest can be found in Table 1. In comparison with previous studies, parents in the current sample demonstrated relatively high level of difficulties in ER and below average level of mentalization, comparable with parents under medium levels of stress in other studies (McMahon & Meins, 2012; Shaffer et al, 2018). In bivariate analyses, difficulties in ER was positively correlated with all three parenting constructs (coercive, submissive, negative feelings); however, mentalization was not significantly correlated with either difficulties in ER or parenting constructs.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Descriptive statistics and correlations for variables of interest can be found in Table 1. In comparison with previous studies, parents in the current sample demonstrated relatively high level of difficulties in ER and below average level of mentalization, comparable with parents under medium levels of stress in other studies (McMahon & Meins, 2012; Shaffer et al, 2018). In bivariate analyses, difficulties in ER was positively correlated with all three parenting constructs (coercive, submissive, negative feelings); however, mentalization was not significantly correlated with either difficulties in ER or parenting constructs.…”
Section: Resultssupporting
confidence: 74%
“…Cronbach’s alpha in Gratz and Roemer’s (2004) study showed excellent internal consistency for both the total score (α = .93) and for the subscales (α > .80). A recent study that identified clusters of regulated and dysregulated mothers reported average DERS scores of 65.11 and 77.02 for well-regulated and dysregulated, respectively (Shaffer, Whitehead, Davis, Morelen, & Suveg, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Third, the results showed that an increase in maternal RSA from baseline to task was positively associated with positive parenting. Previous research has shown that positive parenting is associated with both RSA activation and withdrawal (Leerkes et al, 2017;Lorber & O'Leary, 2005;Moore et al, 2009;Shaffer et al, 2018), but some researchers have argued that different types of tasks and contexts place different demands on physiological systems, and therefore adaptive RSA responses may look different in different contexts (Connell et al, 2017;Cui et al, 2019). For example, RSA withdrawal has been associated with adaptive functioning during stressful tasks (Balzarotti et al, 2017;Connell et al, 2017), but RSA activation has been associated with adaptive functioning and efforts to engage in self-regulation in positive social interactions and to recover from stress (Balzarotti et al, 2017;Butler et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A base of evidence has emerged in the past few years suggesting that associations exist between parenting behavior and RSA reactivity during parent and child interactions (Connell et al, 2017;Shaffer et al, 2018;Skowron et al 2013). In the context of caregiving, parents who engage in more warm and less harsh parenting behavior show higher average RSA scores, compared with baseline, while interacting with their children (Lorber & O'Leary, 2005;Shaffer et al, 2018). Other studies have found greater RSA withdrawal associated with more sensitive and responsive parenting during stressful or challenging parent-child interactions (Leerkes et al, 2017;Moore et al, 2009).…”
Section: Rsa As a Physiological Measure Of Ermentioning
confidence: 99%
“…For within‐family processes, three major pathways that intervene in the link between maternal and child emotion dysregulation are often proposed, including (a) the observation of parental emotion experiences or behaviors, (b) parenting practices that focus on coaching children about emotions and emotion regulation, and (c) the family emotional climate (Morris, Silk, Steinberg, Myers, & Robinson, ). There are many studies focusing on parenting (e.g., Grolnick & Farkas, ; Morelen, Shaffer, & Suveg, ; Morris et al, ; Rutherford, Wallace, Laurent, & Mayes, ; Shaffer, Whitehead, Davis, Morelen, & Suveg, ). Additionally, quite a few studies have examined the family emotional climate in which children's emotion regulation is compromised (Cummings & Schatz, ; Halberstadt & Eaton, ).…”
Section: Introductionmentioning
confidence: 99%